Development of a collect point of eletronic waste - Sigrist, Carolina São Leandro; Fonseca, Luis Felipe Brito; Veiga, Juliana Mendes; Paiva, Jane Maria Faulstich; Moris, Virgínia Aparecida Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
One of the biggest environmental problems faced by the society is related to the lack of suitable sites for the disposal of solid electronics waste in which there are in their composition hazardous and toxic substances to the environment and to the human health. The lack of awareness of a large part of the population regarding the need to conduct an environmentally friendly disposal of these residues is also part of the current reality. These facts which have been intensified by population growth, increased globalization and development of technological sectors, provide a greater focus on the creation of new sustainable policies. The National Policy of Solid Waste (PNRS) stimulated the development of projects related to solid waste management. According to the PNRS, the waste electrical and electronic equipment (WEEE) have the requirement of establishing the reverse logistics by the return of the product after the use of the consumer, for instance, by recycling processes. Yet, there are not enough points of collections and information available to begin the process of collection and proper disposal of WEEE, or agreements among governments, companies, cooperatives and consumers related to this compromise. Hence, this paper has involved the development of a prototype of WEEE collection point in partnership with the sustainable innovation center, Sinctronics. The concern for the prototype design, as well as the evaluation of the best location in the university environment and the media were essential to the collection point to become attractive and useful. The results obtained through observation and questionnaires showed that there has already been an environmental awareness at the university referring to the disposal of waste, however, until that moment, there were not na appropriate collection point and public awareness campaigns for the importance related to the proper disposal of WEEE and information regarding to the rehabilitation process of such waste in the production cycle.